The problem of communication in the context of national consolidation - Dyusalinova, B.K.; Soloshchenko, P.P. (Ye.A.Buketov Karaganda State University Publ., 2014)
The article examines the historical and philosophical approaches to the problem of communication. Its actuality is connected with the Kazakhstan national identity as a defining factor of social status. The idea of open and confidential dialogue constructibility in communication process is being founded as well. The research task of building forms that serve as the language of communication in different social, political and cultural systems is also being actualized in the article.
Ұлттық бірігу контекстіндегі тілдесу мəселесі
Проблема общения в контексте национальной консолидации
Keywords: philosophy; communication; dialogue; mutual understanding; national consensus